Method and Timing of Nitrogen Application In Rainfed Bajra - Singh, S D (Annals of Arid Zone, 2016)
Experiments were conducted over three seasons to integrate timing and method of nitrogen application to bajra such that the effectiveness of fertilizer is maximum and risk in fertilizer use is minimum. Considering results of individual seasons, 30 kg/ha of nitrogen can be added at sowing and 15 kg later as topdressing during normal rainfall years, ’or as spray in moderately dry seasons. Handicapped by lack of spray facilities, 15 kg nitrogen can seldom be applied as topdressing in dry seasons. In that case only 30 kg/ha basal nitrogen is recommended. Time and method of nitrogen application carefully selected could minimise the risk in use of fertili2.er, besides improving N use efficiency.